Assessment of genetic diversity and population structure of Malus sieversii and Malus niedzwetzkyana from Kazakhstan using high-throughput genotyping - Taskuzhina, Aisha; Yanin, Kirill; Khusnitdinova, Marina; Kapytina, Anastasiya; Pozharskiy, Alexandr; Nurtaza, Aidana; Kakimzhanova, Almagul; Khan, Awais; Gritsenko, Dilyara (Tree genetics & genomes, 2025)
Malus sieversii, the primary progenitor of domesticated apples and a vital genetic resource in Kazakhstan, faces increasing threats from aging, degradation, diseases, and insect infestations despite ongoing conservation efforts and the establishment of genetic reserves. The aim of our work was to examine genetic variability, population structure and characterize the alleles of resistance loci for fire blight, apple scab and powdery mildew from M. sieversii and Malus niedzwetzkyana populations in Kazakhstan. We genotyped 352 accessions of M. sieversii and M. niedzwetzkyana sampled from various regions in Kazakhstan using Axiom JKI50kMd SNP array. Wild apple populations from Zhongar Alatau exhibited reduced genetic diversity, with expected heterozygosity (He) of 0.21, and minimal gene flow. In contrast, populations from Ile Alatau demonstrated higher genetic variability, with expected heterozygosity reaching 0.32, likely influenced by gene flow from cultivated apple varieties. Principal component analysis (PCA), clustering, and phylogenetic tree reconstruction consistently identified distinct population groupings corresponding to their geographic origin. Populations from Zhongar Alatau and Tarbagatai formed a relatively homogeneous group, while populations from Ile Alatau and Ketmen clustered into another group, reflecting a higher degree of genetic mixing and heterogeneity. M. niedzwetzkyana emerged as a separate and genetically divergent cluster and demonstrated a higher frequency of polymorphic disease resistance markers compared to M. sieversii , reinforcing its potential as a valuable genetic resource for breeding disease-resistant apple varieties. These findings provide critical insights for conservation strategies, emphasizing the importance of preserving genetic diversity in wild apple populations to support long-term breeding and disease management efforts.